Efektivitas Komunikasi Intereprsonal Kepala Sekolah Dalam Perspektif The 5 Inevitable Laws of Effective Communication di MTs N 1 OKI - Astuti, Mardiah; Marlina, Leny; Fitriyanti, Riska; Andini, Dinda Rizki; Alam, Muhammad Helmi (El-Idare, 2023)
This study aims to describe the effectiveness of interpersonal communication of school principals in the perspective of “The 5 Inevitable Laws of Effective Communication” in MTs Negeri 1 Ogan Komering Ilir. In this study using the research method used is a qualitative method with a phenomenalogical approach. The data collection in this study was through interview, observation, and documentation study techniques. While the data analysis techniques used in this study are data reduction, data presentation, and conclusions. The results showed that the implementation of interpersonal communication of the principal at MTs Negeri 1 Ogan Komering Ilir was quite effective. The development of effective interpersonal communication of school principals is reviewed from “The 5 Inevitable Laws of Effective Communication”, namely the implementation of respect, empathy, audible, clarity, humble. Of course, effective interpersonal communication must also be supported by communicators and communicants.